Role of Organisational Culture of the University in Formation of Psychological Readiness of Students to Assertive Behaviour - Varii, Myron Y.; Leshchynska, Olena A.; Terletska, Yuliana M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: the primary purpose of the work is to study the role of organisational culture of the modern Ukrainian university in the process of formation of psychological readiness of students to assertive behaviour. Background: Scientific and public discussion about reforming the system of higher education requires deeper research of the influence of university organisational culture on forming not only professional but also personal skills and abilities that make this research relevant. Method: The selection has 180 respondents from all departments and institutions of university and has been balanced by gender and age. This was the psychosemantic research. Results: To collect the data, suggestions regarding resistance to undesirable influence were used developed by P. Zimbardo and S. Andersen, ten assertive rules of personality developed by M.J. Smith and the author’s survey "Confession of a sad student". Obtained data were represented using the factor analysis. Assumptions concerning the normal distribution were checked using the statistical criteria of Bartlett of the mathematical, statistical package SPSS 14. Conclusion: The obtained factor structure showed that it is possible to speak of domination in the student environment of the tendency to immature self-affirmation along with a readiness to conquer that can be explained by the inadequate conditions of organisational culture to form assertiveness of student.